Application of compact Non-Evaporable Getter and Sputter Ion Pump combination in UHV system of HIAF. (November 2018) - Luo, C.; Li, P.; Xie, W.J.; Wan, Y.P.; Chai, Z.; Zhu, X.R.; Meng, J.; Chen, S.P.; Yang, W.S.
Abstract: HIAF-BRing, a new multi-purpose accelerator facility of the High Intensity Heavy-Ion Accelerator Facility project, requires an extremely high vacuum lower than 10 −9  Pa to fulfill the requirements of radioactive beam physics and high energy density physics. Use of large speed Titanium sublimation pump (TSP) in combination with Sputter ion pumps (SIP) is not always feasible due to space limitations. A novel combination pump, based on Non Evaporable getter (NEG) and a 10 l/s SIP (NEXTorr ® D 2000-10) has been evaluated as it provides large speed in a more compact design. The two combination pumps (TSP + SIP and NEXTorr D 2000-10) have been tested by dynamic flow method to measure the ultimate pressure, the pumping speed and the suitability for HIAF. Test results show that both combination pumps can be used in the pressure range of 10 −10  Pa. The ultimate pressure of TSP + SIP combination pump is slightly lower than NEXTorr D 2000-10, but the latter one has much larger sorption capacities (H2 : 210200 Pa l vs 265 Pa. l; CO: 430 Pa. l vs 24 Pa. l), which means it is applicable to a wider pressure range. At the same time, after twenty activation cycles, the initial pumping speed of NEXTorr D 2000-10 for H2 and CO decreased less than 10% as compared with the initial pumping speed of the first activation, which meets the actual vacuum system requirement of HIAF. A dedicated vacuum chamber with collimator and NEXTorr D 2000-10 has been designed and manufactured to stabilize the dynamic vacuum by decreasing the heavy ion induced gas desorption and increasing the gas pumping speed. The static and dynamic vacuum pressure evolution has been simulated to verify the feasibility of the NEXTorr D 2000-10 used in the HIAF-BRing. Highlights: Two combination pumps (TSP + SIP and NEXTorr D 2000-10) have been tested to measure the ultimate pressure and the pumping speed. The ultimate pressure of TSP + SIP is lower than NEXTorr D 2000-10, but the sorption capacities of later one are much larger. NEXTorr D 2000-10 can keep absorbing H2 at the pressure 3 × 10 −4  Pa for about 90 h before saturation. The dynamic vacuum pressure evolution has been simulated to verify the feasibility of the NEXTorr D 2000-10 used in BRing.